UPAYA GURU DALAM MEMBANGUN INTERAKSI SISWA MELALUI METODE BELAJAR SAMBIL BERMAIN [TEACHER'S EFFORTS IN BUILDING STUDENT INTERACTION USING A GAME BASED LEARNING METHOD] - Rosarian, Ananda Wini; Dirgantoro, Kurnia Putri Sepdikasari (JOHME: Journal of Holistic Mathematics Education, 2020)
Interaction that occurs in the classroom involves interaction between the teacher and students as well as students and students. One form of class interaction is communication. Communication that is continuously intertwined can also form relationships. A comfortable and pleasant classroom atmosphere is a hope for all class members so that learning objectives can be achieved and can form the class as a shalom community. During the practicum, the writer found that there was no interaction between grade 10 science-track students due to students' individualist attitudes. The teacher as an artist strives and plays a role in creating a pleasant classroom atmosphere through innovative learning methods. Therefore, the writing of this writing aims to find out if the method of learning while playing can build student interaction. The method of learning while playing is one of the innovative, creative, and beneficial learning methods used to increase student interaction and support the achievement of learning objectives. Based on the results of a survey of grade 10 science-track students and mentor feedback, the method of learning while playing using the "Snakes and Ladders" game was proven to be able to increase interaction and relationships between students. However, to see an increase in student interaction consistently, it cannot be measured through one application, but requires a longer time or process. In its application, the teacher also needs to pay attention to the types of educational games used to apply the learning method while playing.BAHASA INDONESIA ABSTRACT: Interaksi yang yang terjadi di dalam kelas melibatkan interaksi antara guru dan siswa maupun siswa dengan siswa. Salah satu bentuk interaksi kelas yaitu adanya komunikasi. Komunikasi yang secara terus menerus terjalin juga dapat membentuk relasi. Suasana kelas yang nyaman dan menyenangkan menjadi harapan bagi seluruh anggota kelas agar tujuan pembelajaran dapat tercapai serta dapat membentuk kelas sebagai komunitas shalom. Dalam masa praktikumnya, penulis mendapati tidak adanya interaksi yang terjalin di antara siswa kelas X-IPA disebabkan oleh sikap individualis siswa. Guru sebagai seorang seniman berupaya dan berperan untuk menciptakan suasana kelas yang menyenangkan melalui metode pembelajaran yang inovatif. Oleh sebab itu, tulisan ini bertujuan untuk mengetahui bahwa metode belajar sambil bermain dapat membangun interaksi siswa. Metode belajar sambil bermain merupakan salah satu metode pembelajaran yang inovatif, kreatif, dan bermanfaat untuk meningkatkan interaksi siswa serta menunjang tercapainya tujuan pembelajaran. Berdasarkan hasil survei terhadap siswa kelas X-IPA dan feedback mentor, metode belajar sambil bermain dengan menggunakan media permainan ular tangga terbukti dapat meningkatkan interaksi serta relasi antar siswa. Namun untuk melihat adanya peningkatan interaksi siswa secara konsisten, tidak dapat diukur melalui satu kali penerapan, namun membutuhkan waktu atau proses yang lebih lama. Dalam penerapannya, guru juga perlu memerhatikan jenis permainan edukatif yang digunakan untuk menerapkan metode belajar sambil bermain.